Magnetically Actuated Manipulation and Its Applications for Cartilage Defects: Characteristics and Advanced Therapeutic Strategies - Zhang, Chi; Cai, You-Zhi; Lin, Xiang-Jin; Wang, Yue (Frontiers in Cell and Developmental Biology, 2020)
For the fact that articular cartilage is a highly organized and avascular tissue, cartilage defects are limited to spontaneously heal, which would subsequently progress to osteoarthritis. Many methods have been developed to enhance the ability for cartilage regeneration, among which magnetically actuated manipulation has attracted interests due to its biocompatibility and noninvasive manipulation. Magnetically actuated manipulation that can be achieved by introducing magnetic nanoparticles and magnetic field. This review summarizes the cutting-edge research on the chondrogenic enhancements via magnetically actuated manipulation, including cell labeling, cell targeting, cell assembly, magnetic seeding and tissue engineering strategies.